LIFE SKILL TRAINING BERBASIS AQUASCAPE PADA PEMUDA NARAPIDANA KASUS NARKOBA DI LAPAS I KOTA MADIUN UNTUK MEWUJUDKAN SDGS - Ayu Safitri, Ayu; Rahmawati, Pebriani; Pratiwingtyas, Lavenia; Rahma Hidayat, Fajar; Lusiana, Restu (Jurnal Pengabdian Kepada Masyarakat Patikala, 2022)
AbstractThis aquascape-based life skill training is a training that not only improves skills, but also hones the abilities, courage, and confidence of young drug convicts. The purpose of this activity is to provide provisions for the youth inmates of the Madiun City I Lapas I drug case in carrying out their lives better after completing their sentences and being accepted by the community again. This activity uses 5 methods, namely the stage of measuring the problems or needs of partners, the stage of realizing the activity, the stage of measuring and evaluating activities, the stage of the core solution of the activity, the stage of the contribution of the parties being considered. The result of these activities is that prisoners inmates with drugs gain new skills in the field of aquascape, gain skills in creating business opportunities and gain skills in product marketing both directly and online. This activity can improve the economic conditions of the prisoners in Madiun City I Lapas I in the creative industry sector. Keywords: Aquascape, Drug Inmates, Madiun City Prison I, Creative Industry